Physiological Evaluation and Correlation between Agnimandhya and Hypothyroidism - Sharma, Harsh; Sharma, Rajesh Kumar; Sharma , Dinesh Chandra (International Research Journal of Ayurveda & Yoga, 2021)
According to Ayurveda Agni (digestive fire) is the most important factor in the process of paaka i.e, digestion and the absorption of the ingested food. Acharyas has classified this Agni into 13 types, i.e. one Jatharagni, five Bhutagni and seven Dhatvagni. Among all the Jatharagni is the most important one, which digests the food and transforms it into Rasa and Mala.(waste product) The decreased intensity of the Jatharagni or weak digestive fire due to various reasons is termed as Agnimandhya (decreases agni) which is the root cause of several disease. Proper regulation and maintenance of Agni is responsible for digestion and maintenance of proper metabolic activities of the body. Thyroid gland is also one of the important glands of the endocrine system. The thyroid gland produces hormones that regulate the body’s metabolic rate, muscle and digestive function, and bone maintenance. Hypothyroidism is the condition in which secretion of Thyroid gland decreases which disturbs the metabolic rate of the body and slows the movement of food through your stomach and intestines. Slower digestion can lead to symptoms like heartburn, constipation, and bloating etc. The normal as well as abnormal function of Thyroid Gland can be correlated with the healthy and altered status of Agni. This article reflects the correlation between the hypothyroidism and Agnimandhya.